Enhancement of complex permittivity and attenuation properties of recycled hematite (α-Fe2O3) using nanoparticles prepared via ball milling technique - Mensah, Ebenezer Ekow; Abbas, Zulkifly; Azis, Raba'ah Syahidah; Khamis, Ahmad Mamoun (MDPI, 2019)
The purpose of this study was to synthesize high-quality recycled α-Fe2O3 to improve its complex permittivity properties by reducing the particles to nanosize through high energy ball milling. Complex permittivity and permeability characterizations of the particles were performed using open-ended coaxial and rectangular waveguide techniques and a vector network analyzer. The attenuation characteristics of the particles were analyzed with finite element method (FEM) simulations of the transmission coefficients and electric field distributions using microstrip model geometry. All measurements and simulations were conducted in the 8–12 GHz range. The average nanoparticle sizes obtained after 8, 10 and 12 h of milling were 21.5, 18, and 16.2 nm, respectively, from an initial particle size of 1.73 µm. The real and imaginary parts of permittivity increased with reduced particle size and reached maximum values of 12.111 and 0.467 at 8 GHz, from initial values of 7.617 and 0.175, respectively, when the particle sizes were reduced from 1.73 µm to 16.2 nm. Complex permeability increased with reduced particle size while the enhanced absorption properties exhibited by the nanoparticles in the simulations confirmed their ability to attenuate microwaves in the X-band frequency range.